Path Feasibility Analysis for String-Manipulating Programs - Bjørner, Nikolaj; Tillmann, Nikolai; Voronkov, Andrei (Microsoft, 2008)
We discuss the problem of path feasibility for programs manipulating strings using a collection of standard string library functions. We prove results on the complexity of this problem, including its undecidability in the general case and decidability of some special cases. In the context of test-case generation, we are interested in an efficient finite model finding method for string constraints. To this end we develop a two-tier finite model finding procedure. First, an integer abstraction of string constraints are passed to an SMT (Satisfiability Modulo Theories) solver. The abstraction is either unsatisfiable, or the solver produces a model that fixes lengths of enough strings to reduce the entire problem to be finite domain. The resulting fixed-length string constraints are then solved in a second phase. We implemented the procedure in a symbolic execution framework, report on the encouraging results and discuss directions for improving the method further.